Knowledge, attitude and practice on the usage of safety helmet among oil palm harvesters - Zolkifli, Nur Zuhairiza; Mohd Tamrin, Shamsul Bahri; Ng, Yee Guan; Mohd Shukoor, Nur Shuhada; Md Akir, Nur Fitriyah; Ng, Gin Siong; Mohd Nasir, Nur Sabrina (Malaysian Public Health Physicians' Association, 2016)
Safety helmet become vital personal protective equipment especially in the plantation in preventing the head from injury. This study evaluate the knowledge, attitude and practice on safety helmet usage among harvesters, the association between knowledge, attitude and practice of safety helmet usage with head injury; and the significant differences of the safety helmet practices before and after the intervention. A cross-sectional study was conducted among 109 harvesters in two oil palm plantation located in Selangor, Malaysia. A set of questionnaire was used to collect the socio demographic background data, knowledge, attitude and practice on the usage of safety helmet. An intervention program through tool box talk on proper usage of safety helmet also was given followed by an observation to look for the differences before and after the tool box promotion on the use of safety helmet. Result from the descriptive analysis showed high score for knowledge, fair score for the attitude and practice among harvesters. There is no association between knowledge (X2=2.733; p>0.05), attitude (X2=2.546; p>0.05) and practice (X2=2.473; p>0.05) with the head injury. The result also gave no significant differences (p>0.05) of the practices before and after the intervention. However, the trends showed decrease in number of practices after the intervention. This study reveals that the knowledge, attitude and practice are not a prominent indicator for head injury among harvesters.